CONTENT ANALYSIS OF NEWSPAPER COVERAGE AND FARMERS’ READERSHIP OF AGRICULTURAL NEWS IN NIGERIA (2013)
Inadequate access to agricultural information contributes largely to low productivity among farmers in Nigeria. The print media has been especially implicated on its low coverage and provision of agricultural information, thus limiting readership among farmers. To validate this observation, the extent of coverage of agricultural news in print media and farmer’s readership were therefore assessed. Content analyses of Nigerian Tribune, New Nigerian, This Day, The Punch and The Comet newspapers as well as questionnaire survey methods were used for carrying out the study. Fett’s seven categories of General news, Pricing and marketing, Government policy, Editorials, Commentaries, Special recommendations and Human interest were used for content analysis. Six hundred and ninety-three agricultural news columns in 960 newspaper editions published between 1999 and 2003 were analysed. Katsina and Lagos states were purposively selected for questionnaire survey. 50 percent of the blocks and cells in the states’ Agricultural Development Projects (ADPs) were randomly selected and 50 percent of farmers’ groups in selected cells were chosen for questionnaire administration resulting in 160 respondents. Personal characteristics and readership of agricultural news were assessed. Data were analysed using descriptive statistics, Chi-square and ANOVA at p=0.05. 80 percent of the farmers were male and 84% were married. Thirty-four percent were in the age bracket of 41-50. Thirty-three percent had between 11 and 14years farming experience and were predominantly crop and livestock farmers. Thirty–three percent of the respondents (33%) purchased and read newspapers. Majority (86.9%) read all categories of agricultural news. Agricultural news was generally not prominently placed in 69.3% of the newspapers. The few prominently placed had 66.8% of them located at the center pages. Government policy category was the most published in the New Nigerian (34.0%), The Punch (33.7%) and This Day (24.4%) newspapers. Special recommendation category was the most published in The Nigerian Tribune newspaper (35%) while general news was the most published in The Comet (21.9%). Clarity of message ranked first in variables that influenced readership of agricultural news while the length of publication ranked least. The Comet had a significantly higher (287.1±2.1) mean number of agricultural news than the New Nigerian (150.0±4.3), The Punch (92.0 ±1.6), This Day (91.0±3.7) and Nigerian Tribune (74.1±6.5). This Day had a significantly higher (405.2 ±3.1) mean size of agricultural news than the Nigerian Tribune (224.2 ±3.5), The Punch (213.1±3.4), The Comet (184.6±3.7) and the New Nigerian (164.6±3.1). Government policy category also had a higher (23.2±2.1) mean than Human interest (17.5±1.9), Special recommendation and General news (16.7±3.9), Pricing and marketing (15.3±2.8), Commentaries (8.51±2.1) and Editorials (2.1±3.2). A significant relationship existed in readership of agricultural news and age χ2=57.9; number of children χ2=28.7, as well as religion χ2=0.357 but not with educational status. A relationship was also identified between the farmers’ readership of agricultural news and categories of agricultural news covered (χ2=.128.7). Reportage and placement of agricultural news were generally poor with differences in number of agricultural news covered across the newspapers; most farmers read all categories of agricultural news published.